Stair-Hexagonal Slot Antenna with Coplanar Waveguide Technique for Biomedical Applications - Rahayu, Yusnita; Hilmi, M. Fadhlurrahman; Wahyu, Yuyu (International Journal of Integrated Engineering, 2020)
Breast cancer is the most common disease suffered by women and increases significantly. Ultra-Wideband (UWB) is a technology that applies electromagnetic signals with wide bandwidth that are currently widely used in the medical field. This research introduces the design of the Stair-Hexagonal slot antenna with the Coplanar Waveguide (CPW) technique which operated at desired frequency of 5.8 GHz. Firstly, the design process of the antenna is adding stair slot to get wide bandwidth. Secondly by adding Hexagonal slot to get the best S11 parameter at the desired frequency. The purpose of antenna is to detect an object in body organs such as tumors and cancer. The antenna is printed and tested. The measured return loss shows that the antenna works well in the desired frequency with wider bandwidth than simulated one. The measured bandwidth of 7.88 GHz is achieved. The gain of the antenna from the simulation is 2.42 dBi and radiation pattern of simulation and measurement are bidirectional, wherein the highest gain is in the rear position. Further analysis is done by comparing the proposed antenna with the existing related works. The result of this research shows the practical usage of the flexible substrate because it can increase the accuracy of object detection.